More-Than-Human Footprints - Victor Muñoz Sanz; Nikos Katsikis (Footprint)
This issue of Footprint explores techn-natural spatialities and materialities found across operational landscapes of primary production. To the extent that these landscapes are increasingly automated and digitised, production and circulation practices are becoming more capital intensive and even less labour-intensive. While amplifying the precarity of human labour, this process relies on appropriating the work of more-than-human assemblages of machines, plants, animals and microorganisms. Central to the focus of this issue is understanding the way these processes are grounded in specific architectural and landscape configurations. In this way, we also aim to complement the debates on past issues of Footprint, offering an investigation of the impact of technological transformations beyond the concentrated landscapes of human inhabitation.